Atypical Presentation of IARS1‐Related Disorder: Expanding the Phenotype and Genotype - Parith Wongkittichote; Kira E. Jonatzke; Benjamin T. Hyde; Lance W. Peterson; Mai He; Robert C. McKinstry; Anthony Antonellis; Marwan Shinawi (JIMD Reports)
ABSTRACT Aminoacyl‐tRNA synthetases (ARSs) catalyze the formation of aminoacyl‐tRNA, which is required for protein translation. A growing number of cases are associated with ARS deficiencies. Pathogenic variants in IARS1 (MIM# 600709), encoding cytoplasmic isoleucyl‐tRNA synthetase, have been associated with autosomal recessive growth retardation, impaired intellectual development, hypotonia, and hepatopathy (GRIDHH, OMIM# 617093). To date, 11 GRIDHH patients have been described. We identified a patient who presented with recurrent episodes of liver failure in the setting of preceding infection and neurocognitive delay, and who recently presented with a clinical picture consistent with chronic nonbacterial osteomyelitis/chronic recurrent multifocal osteomyelitis. Exome sequencing revealed that this patient is compound heterozygous for two IARS1 variants: c.1193dupC;p.(Cys400LeufsTer32) and c.746A>G;p.(Asp249Gly). The frameshift variant is predicted to cause a loss of function, and functional analysis of the p.Asp249Gly variant was performed using baker's yeast. Wild‐type human IARS1 has been shown to support robust yeast growth in the absence of the yeast ortholog, ILS, while human IARS1 harboring p.Asp249Gly could not, indicating a loss‐of‐function effect. The proband was treated with isoleucine supplementation with subjective clinical improvement. Overall, we expand the molecular and clinical spectra of the IARS1‐related disorder, highlight immune dysregulation as a possible novel manifestation of this disorder, and emphasize the utility of a yeast model system for functional studies. A larger cohort of patients is required to validate these observations and evaluate the efficacy of isoleucine supplementation for patients with GRIDHH.